2010
DOI: 10.1002/jso.21617
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral macrophage counts correlate with tumor progression in colorectal cancer

Abstract: Background: The role of intratumoral tumor-associated macrophages (TAMs) in colorectal cancer (CRC) is not clear. We aim to examine the relationships of TAMs and the clinicopathologic features of CRC and the expression of matrix metalloproteinases (MMP)-2 and MMP-9. Methods: Immunohistochemical staining of CD68, MMP-2, and MMP-9 was determined in tissue samples from CRC patients. To test the biological effect of macrophages on tumor cells, cancer cells were cocultured with macrophages and function change of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
106
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 35 publications
(46 reference statements)
1
106
0
Order By: Relevance
“…In contrast, intratumoral TAMs count has been correlated with depth of invasion, lymph node metastasis, and staging of CRC, suggesting that intratumoral macrophages cause cancer cells to have a more aggressive behavior [24,25].…”
Section: Tumor Associated Macrophagesmentioning
confidence: 99%
“…In contrast, intratumoral TAMs count has been correlated with depth of invasion, lymph node metastasis, and staging of CRC, suggesting that intratumoral macrophages cause cancer cells to have a more aggressive behavior [24,25].…”
Section: Tumor Associated Macrophagesmentioning
confidence: 99%
“…There are numerous types of inflammatory cells in the tumor microenvironment, and tumor-associated macrophages (TAMs) are a major component. While the role of TAMs in tumor development is complex and multifaceted, in clinical studies, increased TAM density has been found to be associated with poor prognosis (5)(6)(7). TAMs contribute to tumor development through several mechanisms, including releasing angiogenic factors, promoting tumor cell proliferation, and facilitating tumor cell invasion and metastasis (8).…”
Section: Introductionmentioning
confidence: 99%
“…TAMs, in particular, have been found to be associated with tumor growth and metastasis (5)(6)(7). A large number of studies concerning numerous tumor types, including colorectal cancer (5), supraglottic laryngeal carcinoma (6), Ewing's sarcoma (7), intestinal type gastric cancer (29), pancreatic cancer (30), non-gynecologic leiomyosarcoma (31) and thyroid cancer (32), have shown that the presence of TAMs in the tumor microenvironment is associated with a worse prognosis.…”
mentioning
confidence: 99%
“…43 Tumour-associated macrophages (TAM), whose presence is strongly associated with CRC progression, are the main source of MMP9 in the tumour microenvironment. 44 Of interest, we previously reported elevated levels of circulating MMP-9 in the blood of CRC patients. 45 MMP-9 up-regulation alone, however, is not specific to CRC, as it has also been reported in other malignant tumours and in autoimmune or inflammatory diseases, including ulcerative colitis or lymphocytic colitis.…”
mentioning
confidence: 99%